All the lovers in the night - Kawakami, Mieko, 1976- (Europa Editions, 2022)
Fuyuko Irie is a freelance copy editor in her mid-thirties. Working and living alone in a city where it is not easy to form new relationships, she has little regular contact with anyone other than her editor, Hijiri, a woman of the same age but with a very different disposition. When Fuyoku stops one day on a Tokyo street and notices her reflection in a storefront window, what she sees is a drab, awkward, and spiritless woman who has lacked the strength to change her life and decides to do something about it. As the long overdue change occurs, however, painful episodes from Fuyuko's past surface and her behavior slips further and further beyond the pale. All the Lovers in the Night is acute and insightful, entertaining and engaging; it will make readers laugh, and it will make them cry, but it will also remind them, as only the best books do, that sometimes the pain is worth it.